Mapping the Body of Knowledge of Islamic Broadcasting and Communication: Studi pada Tesis Mahasiswa Magister KPI Tahun 2023–2025 - Nurdin, Ali; Adi, Nur Romdlon Maslahul (UIN Sunan Ampel Surabaya, 2026)
The mapping of the Body of Knowledge (BoK) in the development of the Master’s Program in Islamic Broadcasting and Communication is essential amid the transformation of digital communication and the rapid development of contemporary da‘wah studies. This study aims to map the BoK of the Master’s Program in Islamic Broadcasting and Communication UIN Sunan Ampel Surabaya through an analysis of research trends and themes, research methods, and theories employed in students’ theses from 2023 to 2025. This research employed a qualitative approach using a document study method on students’ theses produced during the 2023–2025 period. The data were analyzed using content analysis techniques assisted by NVivo 12 to identify patterns in research themes, methodologies, and theoretical frameworks. The findings reveal that the dominant research trends include da‘wah communication, digital da‘wah, social media, da‘wah communication strategies, and interpersonal communication. The majority of studies employed qualitative-descriptive methods, with the Miles and Huberman interactive model emerging as the most frequently used data analysis technique. The most widely applied theories include da‘wah communication theory, da‘wah strategy theory, digital media theory, socio-critical and cultural theories, and psychological theories. The study further demonstrates that the BoK of the Master’s Program in Islamic Broadcasting and Communication is evolving toward a digital, multidisciplinary, and transformative paradigm of Islamic communication. However, the research orientation remains largely descriptive and adaptive in nature. Therefore, strengthening digital research methodologies, mixed methods approaches, critical theories, and media studies based on emerging technologies is necessary to enhance the academic competitiveness and innovation of Islamic communication studies at the global level.